Microbial diversity in Antarctic Dry Valley soils across an altitudinal gradient - Mashamaite, Lefentse; Lebre, Pedro H.; Varliero, Gilda; Maphosa, Silindile; Ortiz, Max; Hogg, Ian D.; Cowan, Don A. (Frontiers in Microbiology, 2023)
The Antarctic McMurdo Dry Valleys are geologically diverse, encompassing a wide variety of soil habitats. These environments are largely dominated by microorganisms, which drive the ecosystem services of the region. While altitude is a well-established driver of eukaryotic biodiversity in these Antarctic ice-free areas (and many non-Antarctic environments), little is known of the relationship between altitude and microbial community structure and functionality in continental Antarctica. Here, we analysed prokaryotic and lower eukaryotic diversity across a 684 m altitudinal transect in the lower Taylor Valley, Antarctica.Phylogenetic analysis (based on the sequencing of 16S rRNA and ITS marker gene amplicons) showed clear altitudinal trends in soil microbial composition and structure. In particular Cyanobacteria were more prevalent in higher altitude samples, while the highly stress resistant Chloroflexotai and Deinococcota were more prevalent in lower altitude samples. We also detected a shift from Basidiomycota to Chytridiomycota with increasing altitude.Several genera associated with trace-gas chemotrophy, including Rubrobacter and Ornithinicoccus, were widely distributed across the entire transect, suggesting that trace-gas chemotrophy may be an important trophic strategy for microbial survival in oligotrophic environments. The ratio of trace-gas chemotrophs to photoautotrophs was significantly higher in lower altitudinal samples. Co-occurrence network analysis of prokaryotic communities showed some significant differences in connectivity within the communities from different altitudinal zones, with cyanobacterial and trace-gas chemotrophy-associated taxa being identified as potential keystone taxa for soil communities at higher altitudes. By contrast, the prokaryotic network at low altitudes was dominated by heterotrophic keystone taxa, thus suggesting a clear trophic distinction between soil prokaryotic communities at different altitudes.Based on these results, we conclude that altitude is an important driver of microbial ecology in Antarctic ice-free soil habitats.